Transformasi Digital: Bagaimana Sistem Informasi Mengubah Cara Kerja Organisasi - Abdul Gafar (Jurnal Riset Informatika dan Inovasi, 2026)
Digital transformation is a strategic process that integrates digital technologies into all organizational activities, fundamentally changing the way organizations operate, structure, and build their culture. Information systems play a crucial role in this transformation by enabling data management, business process automation, and data-driven decision making. This article aims to analyze how information systems transform organizational work practices in improving operational efficiency, collaboration, and organizational competitiveness. The method used in this study is a literature review of relevant academic journals and books discussing digital transformation and information systems. The findings indicate that the implementation of information systems accelerates information flow, enhances human resource productivity, and strengthens organizational innovation. However, digital transformation also presents challenges, including resistance to change, limited digital competencies, and information security risks. Therefore, the success of digital transformation requires adaptive leadership, a supportive organizational culture, and an integrated and sustainable information systems implementation strategy.